2005
DOI: 10.1021/jo0503456
|View full text |Cite
|
Sign up to set email alerts
|

The First Fulleropyrrolidine Derivative of Sc3N@C80:  Pronounced Chemical Shift Differences of the Geminal Protons on the Pyrrolidine Ring

Abstract: The first pyrrolidine adduct on Sc(3)N@C(80) was synthesized and fully characterized. Addition of the N-ethylazomethine ylide occurs regioselectively on a [5,6] double bond on the surface of the icosahedral symmetry Sc(3)N@C(80), exactly in the same position as that described previously for a Diels-Alder adduct of the same compound.(11a,b) This addition pattern results in symmetric pyrrolidine carbons and unsymmetric geminal hydrogens on the pyrrolidine ring, as confirmed by (1)H and (13)C NMR spectroscopy, es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
124
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(134 citation statements)
references
References 48 publications
7
124
0
3
Order By: Relevance
“…In the same year Echegoyen and co-workers reported another separation method for the I h isomer from the isomeric mixture (D 5h and I h ) of Sc 3 N@C 80 which involved the selective synthesis of N-ethylpyrrolidino-Sc 3 N@C 80 . [53,61] Under certain reaction conditions only the I h isomer reacts, even in the presence of Sc 3 N@C 78 . Once the pyrrolidino adduct is isolated it is heated at reflux with maleic anhydride to recover the pure I h isomer.…”
Section: Alternative Purification Methods Of Emfsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the same year Echegoyen and co-workers reported another separation method for the I h isomer from the isomeric mixture (D 5h and I h ) of Sc 3 N@C 80 which involved the selective synthesis of N-ethylpyrrolidino-Sc 3 N@C 80 . [53,61] Under certain reaction conditions only the I h isomer reacts, even in the presence of Sc 3 N@C 78 . Once the pyrrolidino adduct is isolated it is heated at reflux with maleic anhydride to recover the pure I h isomer.…”
Section: Alternative Purification Methods Of Emfsmentioning
confidence: 99%
“…This showed that the pyrrolidine ring was formed regioselectively at a [5,6] bond of the Sc 3 N@C 80 (I h ) isomer. [53] The same year, Echegoyen and co-workers reported the first pyrrolidine adduct of Y 3 N@C 80 (I h , 13 b; Scheme 5), but the cycloaddition occurred at a [6,6] bond for this metallic nitride EMF. [54] Later, Dorn, Gibson, and co-workers reported the functionalization of M 3 N@C 80 (M = Sc, Er) with N-methylglycine and 13 C-formaldehyde, and they observed a similar addition to a [5,6] bond as observed with the Sc 3 N@C 80 (I h ) isomer.…”
Section: [3+2] Cycloadditions: 13 Dipolar Cycloaddition or Prato Reamentioning
confidence: 97%
See 1 more Smart Citation
“…A photoinduced electron-transfer reaction in the Sc 3 N@C 80 -Fc donor-acceptor dyad 138 was reported. 137 N-methyl-2-ferrocenyl [5,6]-Sc 3 N@I h -C 80 -fulleropyrrolidine was prepared by thermal reaction of Sc 3 N@I h -C 80 with sarcosine and ferrocenecarboxaldehyde in a toluene/ o-dichlorobenzene (o-DCB) mixture.…”
Section: Iii1b Metallofullerenesmentioning
confidence: 99%
“…Functionalization of Sc 3 N@C 80 has been accomplished using both a Diels-Alder reaction and an azomethine ylide addition. 16,17 In the case of Diels-Alder reaction, addition products were formed at the 5:6 ring junction of the C 80 cage. On the other hand, azomethine ylide addition to Y 3 N@C 80 produced an adduct at the 6:6 ring junction.…”
Section: Introductionmentioning
confidence: 99%